Taher Ahmed Makki’s Views on the Concept of the Short Story and Its Application in the Arabic Short Stories: Literature - Mohd Ismath, Nurul Hanilah; Samsuri, Maimanah (Al-Ḍād Journal, 2022)
This study talks about Al-Tahir Ahmed Makki’s views on the concept of the Arabic short story from its characteristics and elements, as the modern Arab short story at its beginning was derived from the Western short story, through which the research seeks to see the congruence of the story’s views of Al-Tahir Ahmed Makki in some of the short stories selected in his book. The research employs library research approach and the analytical approach in the study, where the study used the library research approach by looking at the main source, which is the short story book Studies and Selections by Taher Ahmed Makki, as well as other sub-sources including refereed journals, scientific articles, theses and other reference books. As for the analytical method, the study used the two stories in the book for analysis, using his views on this issue. Keywords: Taher Ahmad Makki, issues in Arabic short stories, examples of short stories